Introduction to economic analysis in the African Trypanotolerant Livestock Network - McIntire, John M. (ILCA/ILRAD, 1988)
Examines background to some of the economic analysis done in the African Trypanotolerant Livestock Network; defines some models of animal production; presents results of experiments with the ILCA microcomputer herd model about some important problems in the Network and projects returns to gains of animal production in Africa